An Improving Service Quality Using Servqual With 3 Fuzzy Numbers : A Study in ITESA Muhammadiyah Semarang - Tarita Intan Soraya; Ratri Wulandari; Wellie Sulistijanti; Wulan Bhakti Pertiwi; Muhammad Sulthan Madany (Lembaga Pengembangan Kinerja Dosen, 2025)
Ensuring the delivery of high-quality public services within educational institutions is a critical factor for sustaining student satisfaction, institutional reputation, and overall organizational credibility. Service quality in higher education is often multidimensional and subjective, making its evaluation a challenging process. To address this complexity, the present study integrates the traditional Servqual model with fuzzy logic in order to handle the uncertainty and vagueness associated with human perceptions. The Servqual framework emphasizes five core dimensions of service quality, namely tangibles, reliability, responsiveness, assurance, and empathy, which together provide a comprehensive understanding of institutional service performance. The research was conducted at ITESA Muhammadiyah Semarang, where data collection was carried out through structured questionnaires designed to measure both student expectations and actual perceptions regarding institutional services. In order to capture the imprecise nature of these responses, three types of fuzzy numbers—triangular, trapezoidal, and shoulder fuzzy numbers—were applied to convert the linguistic assessments into measurable values. Subsequently, fuzzy gap analysis was performed to evaluate the discrepancy between expectations and perceptions across the five Servqual dimensions. The results of this analysis highlight that the integration of fuzzy logic into the Servqual model provides a more nuanced and flexible framework for assessing service quality compared to the conventional approach. It reduces the ambiguity in interpreting survey responses, thereby yielding more reliable insights into areas where service performance falls short of expectations. Furthermore, the study demonstrates that each dimension contributes differently to overall satisfaction, with responsiveness and assurance emerging as critical aspects requiring attention. In conclusion, the fuzzy-based Servqual model offers a robust methodological advancement in evaluating service quality within educational settings. The findings not only inform institutional leaders about current performance gaps but also provide actionable insights for continuous quality enhancement, policy formulation, and strategic decision-making to strengthen institutional competitiveness and credibility.